Comparison of Nitrate Isotopes Between the South China Sea and Western North Pacific Ocean: Insights Into Biogeochemical Signals and Water Exchange. Issue 5 (27th April 2022) - Yang, Jin‐Yu Terence; Tang, Jin‐Ming; Kang, Sijing; Dai, Minhan; Kao, Shuh‐Ji; Yan, Xiuli; Xu, Min Nina; Du, Chuanjun
Abstract: Reconstructing past changes in the oceanic nitrate inventory with sedimentary N records in the South China Sea (SCS), which is the terminal of North Pacific Intermediate Water (NPIW), has regional and global implications. However, water‐column nitrate cycling that affects N isotope preservation remains poorly understood in the SCS. We present a new data set of nitrate isotopes ( δ 15 N NO 3 ${δ }^{15}{N}_{{\text{NO}}_{3}}$ and δ 18 O NO 3 ${δ }^{18}{O}_{{\text{NO}}_{3}}$ ) to elucidate nitrate dynamics in the SCS and the adjoining western North Pacific Ocean (wNPO). Greater increases in δ 18 O NO 3 ${δ }^{18}{O}_{{\text{NO}}_{3}}$ than in δ 15 N NO 3 ${δ }^{15}{N}_{{\text{NO}}_{3}}$ are observed in the SCS euphotic zone, suggesting a combined effect of partial nitrate assimilation and nitrification. In the subsurface and thermocline waters of both regions, upward disproportional decreases in δ 15 N NO 3 ${δ }^{15}{N}_{{\text{NO}}_{3}}$ and δ 18 O NO 3 ${δ }^{18}{O}_{{\text{NO}}_{3}}$ accompanied by elevated nitrate anomalies (N*) indicate an accumulation of external N. Such changes are less significant in the SCS due to higher nitrate concentrations therein, although external N influxes are comparable in both regions. High δ 15 N NO 3 ${δ }^{15}{N}_{{\text{NO}}_{3}}$ and δ 18 O NO 3 ${δ }^{18}{O}_{{\text{NO}}_{3}}$ values in the wNPO intermediate water result from the lateral transport of NPIW with isotopically more enriched nitrate from the remote denitrification zones followed by mixing with overlying water containing isotopically depleted nitrate. As NPIW flows into the SCS, its isotopically enriched signal is further diluted by strong vertical mixing with overlying and underlying waters in the interior. Compared to its source water from the wNPO, the SCS deep water has consistent nitrate isotopic compositions but significantly lower N*, indicating increased benthic denitrification at the wNPO margins with an estimated rate of 0.26–0.41 mmol N m −2 day −1 . Plain Language Summary: The South China Sea (SCS) is an ideal region to study past changes in the oceanic N pool using sedimentary N records. These records are sensitive to water‐column nitrate cycling. This study presents a new data set of nitrate isotopes in the SCS and the neighboring western North Pacific Ocean, the aim of which is to determine major processes controlling their distribution. Partial nitrate consumption by phytoplankton and nitrate production from ammonium/nitrite oxidation by microorganisms together determine nitrate isotopes in the upper 100 m of the SCS. Atmospheric‐derived and biologically fixed N that provides lighter nitrate isotopes mainly accumulates in the subsurface water (100–400 m). In deeper waters, the distribution of nitrate isotopes in the SCS is regulated by a vertical sandwich‐like water flow structure through the Luzon Strait, that is westward inflows of the North Pacific waters in the upper (<750 m) and deep (>1, 500 m) layers and an eastward outflow of SCS waters between the two layers. Strong vertical mixing in the SCS interior further smooths the original nitrate isotopes. Our findings highlight the important role of these biogeochemical and physical processes in governing water‐column nitrate isotopes and thus sedimentary N records in the SCS. Key Points: Nitrate δ 15 N and δ 18 O increase unequally in the South China Sea (SCS) surface water due to partial nitrate assimilation and nitrification External N inputs lower δ 15 N and δ 18 O of subsurface nitrate to a lesser extent in the SCS than in the western North Pacific Ocean (wNPO) Lateral exchange between SCS and wNPO intermediate and deep waters along with vertical mixing modifies their nitrate isotopic composition